Tapered optical fiber DNA biosensor for detecting Leptospira DNA - Lam, Jia-Yong; Yaacob, Mohd Hanif; Chee, Hui-Yee (Medknow Publications, 2023)
Objective: To establish a DNA detection platform based on a tapered optical fiber to detect Leptospira DNA by targeting the leptospiral secY gene. Methods: The biosensor works on the principle of light propagating in the special geometry of the optical fiber tapered from a waist diameter of 125 to 12 μm. The fiber surface was functionalized through a cascade of chemical treatments and the immobilization of a DNA capture probe targeting the secY gene. The presence of the target DNA was determined from the wavelength shift in the optical transmission spectrum. Results: The biosensor demonstrated good sensitivity, detecting Leptospira DNA at 0.001 ng/μL, and was selective for Leptospira DNA without cross-reactivity with non-leptospiral microorganisms. The biosensor specifically detected DNA that was specifically amplified through the loop-mediated isothermal amplification approach. Conclusions: These findings warrant the potential of this platform to be developed as a novel alternative approach to diagnose leptospirosis.